A new species Pinnularia lacustrigibba sp. nov. within the Pinnularia subgibba group (Bacillariophyceae). Issue 3 (3rd July 2018) - Poulíčková, Aloisie; Kollár, Jan; Hašler, Petr; Dvořák, Petr; Mann, David G.
Abstract : Some traditional diatom species have long been considered 'cosmopolitan', i.e., they are ubiquitous in suitable habitats. However molecular methods have revealed that some of these diatoms are complexes consisting of a few or many species, whose identification by eye with LM is difficult or impossible. This is true of several groups within Pinnularia, including the P. subgibba group, in which molecular species delimitation based on cox1-5P and D1–D3 LSU rDNA markers revealed 15 species within a dataset of 58 unique genotypes, representing 105 strains of the group. One clade comprises reproductively compatible clones from Scottish lakes and its morphology does not correspond exactly to any of the known Pinnularia species; thus the description of a new species ' P. lacustrigibba ' sp. nov. is proposed.